The battle of the Labyrinth - Riordan, Rick (New York Hyperion Books for Children, 2008)
When demonic cheerleaders invade his high school, Percy Jackson hurries to Camp Half Blood, from whence he and his demigod friends set out on a quest through the Labyrinth, while the war between the Olympians and the evil Titan lord Kronos draws near
I battle the cheerleading squad -- The underworld sends me a prank call -- We play tag with Scorpions -- Annabeth breaks the rules -- Nico buys happy meals for the dead -- We meet the God with two faces -- Tyson leads a jailbreak -- We visit the Demon Dude Ranch -- I scoop poop -- We play the game show of death -- I set myself on fire -- I take a permanent vacation -- We hire a new guide -- My brother duels me to the death -- We steal some slightly used wings -- I open a coffin -- The lost God speaks -- Grover causes a stampede -- The council gets cloven -- My birthday takes a dark turn
the new york times 1 best-selling series
1
Keywords: Animals, Mythical -- Fiction; Camps -- Fiction; Monsters -- Fiction; Mythology, Greek -- Fiction